Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Dim Sum Frozen Food Kunyah.Inaja di Cengkareng - Sembiring, Vienna Artina; Prabandari, Wijayanti Dewi; Sari, Melanie Indah (Jurnal Ilmiah Pariwisata, 2023)
The aim of the research is to determine the effect of service quality on customer satisfaction of Dim Sum Frozen Food Kunyah.Inaja in Cengkareng. The method used in this research is a quantitative descriptive method, a sampling technique, namely an accidental sampling technique, data obtained from the results of distributing questionnaires to all customers who bought food at Kunyah.inaja, a total of 83 respondents. Based on the research results, it is stated that there is an influence of Service Quality on Customer Satisfaction at Kunyah.inaja Cengkareng. The quality of service at Kunyah.inaja has a positive impact on customer satisfaction, with high quality contributing to loyalty, preventing customer turnover, and various other benefits. Kunyah.inaja's success in providing superior services supports operational efficiency, advertising effectiveness, and improves business reputation, with customer satisfaction as the main key to maintaining and improving their position in the market. Suggestions for Sum Frozen Food Kunyah.Inaja in Cengkareng regarding service quality are: (1) Maintain consistent quality raw materials; (2) Provide employee training for interpersonal skills and product knowledge; (3) Monitor and evaluate the service process; (4) Quick response to customer complaints, because satisfaction is often formed from the experience of handling positive complaints. Keywords: Service Quality, Customer Quality